'We Went Bravely On ... ': The Theatre and Spectacle of Everyday Life in British Written Representations of Colonial South Asia. - Smith, Ellen (Journal of Imperial & Commonwealth History, 2023)
Analysing how British women and men in nineteenth and twentieth-century colonial South Asia made 'theatre' or 'spectacles' of everyday life in personal correspondence, this article examines the foundations of a particular kind of imagery of empire which often survived beyond decolonisation. It examines constructions of the quotidian in different arenas of the colonial experience – the ship, the environment and climate, and the household – to consider the textual, epistolary and discursive tools that writers used to feed seemingly innocuous details about daily life into the broader coercive work of the British Empire. The British in India reconfigured the everyday into a 'spectacle', framing experiences as imperial burden and sacrifice. The article uses a selection of personal, unpublished letters written by British women and men in India, to show how they rendered themselves as spectacles, staging everyday life as a theatre in which to construct identity and convey racial and cultural difference, and from which to be 'seen' educating and 'civilising' and struggling against domestic servants. In particular, this article uses the revealing, and hitherto unexamined, correspondence of missionary wife Agnes May Johnston between 1915 and 1926 from Calcutta, written to her family in Wolverhampton, England. The upkeep of regular communications about the discomfort and dangers of travel, the oppressive climate, and the maintenance of order within the household, allowed correspondents to fashion themselves as 'out of place' and incongruous with the colonial environment, thereby affirming their Britishness and stabilising imperial identity. The article conceptualises everyday life as an imperial construction in these terms, and foregrounds 'the familiar' in historical, literary and postcolonial analytical frameworks. In doing so it demonstrates how imperial conceptions of power operated through the language, gestures, and behaviours that texture day-to-day experiences, and which shape, in the process, a specific imperial gaze.